(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
In this article, gender – Women and men’s relations are manifested in all spheres of life and activity of society, including politics, economics, law, culture, education, science. In addition to the development trend of Western and Eastern Tamaddun, the specific aspects of eastern gender equality are also covered in the example of the views of allomas.